Anglicans, Puritans and American Indians: Persecution or Toleration? - Porter, H. C. (Studies in church history, 1984)
‘Go ye into all the world, and preach the Gospel to every creature’ (Mark 16: 15). Modern historians find it fashionable to categorise Missions as examples of Cultural Conflict. Members of the ethnohistorical school—concerned especially with the meeting and blending of Indian and European ways of life—present Conversion as a species of Persecution: an infringement of Indian human rights, an exercise in ethnocentrism or exploitative capitalism—part of the Cant of Conquest. Conversion—the colonialisation of a native belief system—means ‘acculturation’, ‘deculturation’, or tragic ‘despiritualisation’. Accounts of the relation between Indians and English colonists in colonial North America take a hint from the complaint of Roger Williams of Rhode Island, writing in 1654 to the authorities of Massachusetts about the destructive wars, cruel and unnecessary, against the tribes of New England. Christianity means conquest, harsh and brutal. Some of this emphasis on atrocities may spring from historians’ indignation at Christian activities apparently so alien to the Sermon on the Mount.